Penyuluan Vitamin A Di Kampung Botol Wilayah Puskesmas Jalan Gedang - Maulani, Nurul; Nababan, Lolli; Oktaviani, Vina; Aprilia, Widia; Sari, Erna (Gayaku Publisher, 2022)
The purpose of this counseling is to increase the knowledge of cadre mothers and mothers who have babies, toddlers about the importance of Vitamin A. The method used in this service is counseling carried out in Kampung Botol Village, Jalan Gedang Health Center, Regency. increasing knowledge about vitamin A as a government program which was carried out in August and February.